Report of the Village and Small Scale Industries (Second Five Year Plan) Committee 1955 - Planning Commission (Planning Commission Government of India, 1955)
The report of the Village and Small Scale Industries Committee under the Second Five-Year Plan outlines strategic measures to promote rural and small-scale industries as drivers of economic growth and employment in India. The plan aims to increase national income by 25% and generate 10–12 million new jobs through decentralized production, technical improvements, and cooperative organization. Specific focus areas include cotton, silk, and wool weaving, handloom modernization, sericulture, coir, vegetable oil, and leather industries. Employment estimates highlight potential job creation across multiple sectors, supported by targeted financial allocations and infrastructure. The report emphasizes institutional coordination, including the establishment of a dedicated Ministry for Small-Scale and Village Industries, training programs, and regional service institutes. Marketing strategies, housing for artisans, and research initiatives are recommended to enhance productivity, stabilize incomes, and ensure sustainable growth. Overall, the report envisions a cooperative, decentralized, and skill-driven industrial framework to strengthen rural economies and contribute to inclusive national development.
Government of India Planning Commission
Keywords: Village Industries; Small-Scale Industries; Handloom; Employment Generation; Decentralization; Cooperative Societies; Technical Training; Marketing Strategies; Yarn Production; Sericulture; Khadi; Industrial Development